A national e-Delphi towards the measurement of safe medication practices in Portuguese hospitals - Guerreiro, Mara Pereira (2016)
Objectives To determine the face and content validity of items for measuring safe medication practices in Portuguese hospitals. Methods 128 items were drafted from content analysis of existing questionnaires and the literature, employing preferred terms of the WHO International Classification for Patient Safety (Portuguese version). A two-round e-Delphi was convened, using a purposive multidisciplinary panel. Hospital-based experts were asked to rate the relevance of items on a 7-point Likert scale and to comment on their clarity and completeness. Results The response rate was similar in both rounds (70.3% and 73.4%, respectively). In the first round 91/128 (71.1%) items reached the predefined level of positive consensus. In the second round 23 additional items reached positive consensus, as well as seven items newly derived by the panel. Conclusions Most items have face and content validity, indicating relevance and clarity, and can be included in a future questionnaire for measuring safe medication practices in Portuguese hospitals.